JNK Suppresses Tumor Formation via a Gene-Expression Program Mediated by ATF2 - Malgorzata Gozdecka; Stephen Lyons; Saki Kondo; Janet Taylor; Yaoyong Li; Jacek Walczynski; Gerald Thiel; Wolfgang Breitwieser; Nic Jones (Cell Reports, 2014)
JNK and p38 phosphorylate a diverse set of substrates and, consequently, can act in a context-dependent manner to either promote or inhibit tumor growth. Elucidating the functions of specific substrates of JNK and p38 is therefore critical for our understanding of these kinases in cancer. ATF2 is a phosphorylation-dependent transcription factor and substrate of both JNK and p38. Here, we show ATF2 suppresses tumor formation in an orthotopic model of liver cancer and cellular transformation in vitro. Furthermore, we find that suppression of tumorigenesis by JNK requires ATF2. We identify a transcriptional program activated by JNK via ATF2 and provide examples of JNK- and ATF2-dependent genes that block cellular transformation. Significantly, we also show that ATF2-dependent gene expression is frequently downregulated in human cancers, indicating that amelioration of JNK-ATF2-mediated suppression may be a common event during tumor development.